2020
DOI: 10.1080/01652176.2019.1707907
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance (NMR)-based metabolome profile evaluation in dairy cows with and without displaced abomasum

Abstract: Erdem Gulersoy (2020) Nuclear magnetic resonance (NMR)-based metabolome profile evaluation in dairy cows with and without displaced abomasum, Veterinary Quarterly, 40:1, 1-15, ABSTRACT Background: Displaced abomasum (DA) is a condition of dairy cows that severely impacts animal welfare and causes huge economic losses. Objective: To assess the metabolic status of the disease using metabolomics in serum, urine and liver samples aimed at both water soluble and lipid soluble fractions. Methods: Fifty Holstein mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 45 publications
4
26
1
1
Order By: Relevance
“…Interestingly, Xu et al [39] found no correlation between calculated energy balance in early lactation dairy cows and the concentrations of any of the branched-chain amino acids or lactate. Conversely, when compared to healthy controls, cows with fatty liver and displaced abomasa have been shown to have lower serum alanine concentrations [27,29], and cows with ketosis have lower lactate and alanine concentrations [25,42]. This suggests that alterations in glucogenic precursors, in particular lactate and alanine, are indicative of a perturbed metabolism, not simply negative energy balance.…”
Section: Similarities Between Bhba and Nefamentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Xu et al [39] found no correlation between calculated energy balance in early lactation dairy cows and the concentrations of any of the branched-chain amino acids or lactate. Conversely, when compared to healthy controls, cows with fatty liver and displaced abomasa have been shown to have lower serum alanine concentrations [27,29], and cows with ketosis have lower lactate and alanine concentrations [25,42]. This suggests that alterations in glucogenic precursors, in particular lactate and alanine, are indicative of a perturbed metabolism, not simply negative energy balance.…”
Section: Similarities Between Bhba and Nefamentioning
confidence: 99%
“…Untargeted metabolomics combines high throughput molecular analytical techniques such as proton nuclear magnetic resonance ( 1 H NMR) spectroscopy with multivariate statistical modelling, to characterize the metabolic response of a biological system to pathophysiological stimuli [24]. Examples in dairy cattle include studies of ketosis [25,26], fatty liver [27], hypocalcaemia [28] and displaced abomasa [29]. The collective metabolic features of a given state or condition can be described as its "metabolomic fingerprint".…”
Section: Introductionmentioning
confidence: 99%
“…The authors show that 1H-NMR can assess relevant metabolites involved in milk quality both from a nutritional and industrial perspective. Basoglu and coworkers [ 44 ] compared the metabolic status of healthy Holstein dairy cows with those suffering from displaced abomasum (a core component of the ruminant stomach that typically resides on the abdomen’s floor fills with gas and rises to the top of the abdomen). The author found the risk of fatty liver and ketosis incremented considerably in cows with displaced abomasum.…”
Section: Selected Instrumental Techniques and Their Applicationsmentioning
confidence: 99%
“…Another aim of dairy cattle metabolomic studies is to identify biomarkers which enable early identification of health disorders in the transition period such as ketosis [8,9], hypocalcemia [10] and displaced abomasa [11]. Of particular interest are studies that have identified biomarkers that are predictive of transition period disorders, such as that by Hailemariam et al [12], who identified a panel of three metabolites that could predict the occurrence of peri-parturient disease up to four weeks before calving.…”
Section: Introductionmentioning
confidence: 99%